MAKING SENSE OF ETHNOGRAPHY: FROM AN OUTSIDER PERSPECTIVE - Savira, Siti Ina (Universitas Negeri Surabaya, 2011)
his paper is aimed to compare two ethnographic works Learning to Labour (Willis, 1977), and Masculinity Beyond the Metropolis (Kenway, Kraack, & Hickey-Moody, 2004). The comparison is expected to illustrate how to make sense ethnographic work as a research methodology with its various types of epistemology and approach. The review will begin with a brief outline of the studies as described in each book and follow with further elaboration directed by several headings that covers Crotty (1998) four elements, namely epistemology, theoretical perspective, methodology, and method. It will also discuss the knowledge and values, and the theory of culture of each study.